Thread-like tentacles in the Mediterranean corals Paramuricea clavata and Corallium rubrum - LOPEZ-GONZALEZ, PABLO J; BRAMANTI, LORENZO; ESCRIBANO-ÁLVAREZ, PABLO; BENEDETTI, MARIA-CARLA; MARTÍNEZ-BARALDÉS, IRENE; MEGINA, CÉSAR (Mediterranean Marine Science, 2018)
The occurrence of modified tentacles (i.e. thread-like tentacles) in the Mediterranean octocorals Paramuricea clavata and Corallium rubrum is reported. Colonies of four species of Mediterranean gorgonians were maintained in aquarium conditions for more than 5 months. The development of thread-like tentacles has been observed only in two of the four species. The presence of modified tentacles in other cnidarians has been usually associated with defensive/aggressive behavior. Our observations showed that thread-like tentacles in P. clavata and C. rubrum can also be used for feeding.